A new extension of the FGM copula with an application in reliability. Issue 9 (25th March 2022) - Ebaid, Rasha; Elbadawy, Walid; Ahmed, Essam; Abdelghaly, Abdalla
Abstract: We propose a new symmetric extension of the bivariate Farlie-Gumbel-Morgenstern (FGM) copula with given marginals. The main feature of this new extension is the higher dependence level it permits between random variables. It is shown that the range of Spearman's Rho is [ − . 33,   0.375 ] . We use this new extension to estimate reliability in a dependent stress-strength model with an application to the Egyptian finance system.